Method for electrochemical treatment of nitrate waste water and application in synthesis of ammonia

By using a carbon nanotube catalyst with built-in phosphorus-doped copper oxide and a cascade membrane configuration, the problems of high catalyst cost and mismatch of active hydrogen supply in the electrolytic treatment of nitric acid wastewater were solved, achieving a highly efficient conversion of nitrates to ammonia.

CN122831439BActive Publication Date: 2026-11-06HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611327739.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-11-06
Estimated Expiration
2046-08-31

AI Technical Summary

Technical Problem

Existing catalysts for the electrolytic treatment of nitric acid wastewater are costly and have mismatched active hydrogen supply, resulting in low nitrate conversion efficiency and easy occurrence of side reactions.

Method used

Using carbon nanotubes with built-in phosphorus-doped copper oxide as a catalyst, the electrocatalytic reduction of nitrate in a neutral environment is achieved through a cascade configuration of bipolar membrane and cation exchange membrane. The capillary effect of carbon nanotubes and phosphorus doping are utilized to improve the generation and utilization of active hydrogen and prevent side reactions.

Benefits of technology

This improved the conversion efficiency of nitrate and the selectivity of ammonia, achieving efficient nitrate removal and ammonia recovery while reducing the cost of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122831439B_ABST
    Figure CN122831439B_ABST
Patent Text Reader

Abstract

This invention discloses a method for electrochemically treating nitrate wastewater and its application in ammonia synthesis, belonging to the field of nitrate wastewater treatment and ammonia recovery technology. This invention solves the problems of high catalyst cost and mismatched active hydrogen supply in existing electrolytic treatments of nitrate wastewater. This invention uses an electrode prepared with a catalyst as the cathode and Ag / AgCl as the reference electrode for electrolytic treatment of nitrate wastewater. The catalyst used is carbon nanotubes with embedded phosphorus-doped copper oxide. In this invention, acidification reflux opens both ends of the carbon nanotubes, followed by two high-temperature pyrolysis processes to form a carbon nanotube catalyst with embedded phosphorus-doped copper oxide. The copper oxide enhances nitrate conversion, and phosphorus doping weakens excessive hydrogen evolution from the copper oxide. Simultaneously, the two-dimensional structure of the carbon nanotubes further optimizes the interfacial water supply, preventing hydrogen evolution reactions. In this invention, the ammonia-containing solution reduced in the cathode chamber is fixed in the acid chamber as ammonium salt using a hollow fiber gas diffusion membrane, while sodium hydroxide can be recovered in the alkali chamber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nitrate wastewater treatment and ammonia recovery technology, and relates to a method for electrochemical treatment of nitrate wastewater and its application in ammonia synthesis. Background Technology

[0002] With the acceleration of industrialization and urbanization, the discharge of nitrate-containing wastewater is increasing daily. Nitrates are highly soluble in water and difficult to remove by conventional methods. Indiscriminate discharge leads to eutrophication, disrupts the aquatic ecosystem, and threatens drinking water safety. Therefore, finding efficient and economical nitrate wastewater treatment technologies has become a critical issue urgently needing resolution. Among numerous treatment methods, electrocatalytic nitrate reduction technology, under controllable electrochemical conditions, utilizes an electrocatalyst to gradually reduce nitrate nitrogen at the cathode, ultimately converting it into low-toxicity or usable products such as nitrogen gas or ammonia. This not only effectively degrades nitrate pollutants in water but also enables nitrogen resource recovery to a certain extent. In particular, the pathway of reducing nitrate nitrogen to ammonia avoids the high energy consumption, difficult process control, and reaction risks and uncontrollable factors associated with the traditional Haber-Bosch process for high-temperature, high-pressure ammonia synthesis. Compared to previous pathways, this technology allows for reaction regulation under relatively mild conditions, providing new possibilities for the removal and resource utilization of pollutants from nitrate-containing wastewater. However, the selection and performance of electrocatalytic materials remain key issues restricting the large-scale application of this technology in practical wastewater treatment.

[0003] Commonly used electrocatalytic materials are mostly based on noble metals or their composite systems. While they possess good catalytic capabilities, they generally suffer from high costs, limited reserves, and easy decay of surface active sites during the reaction process. In contrast, catalytic materials based on the transition metal copper have significant economic advantages and feasibility in practical applications due to their low cost and excellent catalytic activity towards nitrate systems. Meanwhile, the rational generation and utilization of active hydrogen remains a key issue in the preparation of high-performance electrocatalysts. Elemental copper, due to its relatively low activity for nitrate conversion and limited ability to dissociate water, easily leads to the accumulation of intermediate products such as nitrite during the reaction, resulting in poisoning of the catalyst surface or active sites, reducing overall conversion efficiency and stability. On the other hand, copper oxide, due to its strong adsorption and dissociation tendency towards water, can generate excess active hydrogen. Although this is beneficial for hydrogen source supply, it easily triggers side reactions such as hydrogen evolution, leading to decreased selectivity and affecting nitrate removal.

[0004] To address the contradictions such as insufficient matching between hydrogen source supply rate and reaction requirements, as well as the accumulation of intermediate products or exacerbation of side reactions in the aforementioned catalytic process, it is necessary to develop a method that can regulate the adsorption and dissociation behavior of materials on water, while simultaneously influencing the nitrate conversion process, thereby fundamentally improving the generation and utilization efficiency of active hydrogen, and achieving the removal of nitrates from wastewater and the efficient synthesis of ammonia. Summary of the Invention

[0005] To address the problems of high catalyst cost and mismatched active hydrogen supply in existing electrolytic treatments of nitrate wastewater, this invention provides a method for electrochemical treatment of nitrate wastewater and its application in ammonia synthesis.

[0006] The technical solution of the present invention is as follows: One objective of this invention is to provide a method for electrochemically treating nitrate wastewater. The method involves using an electrode prepared with a catalyst as the cathode, Ag / AgCl as the reference electrode, and a platinum sheet, ruthenium-iridium-titanium electrode, or boron-doped diamond electrode as the anode to electrolyze water containing nitrate ions. The catalyst is a carbon nanotube with embedded phosphorus-doped copper oxide.

[0007] Further specified, the voltage between the cathode and the reference electrode is 0.4-0.9V vs. RHE.

[0008] Further specifying, the cathode preparation method is as follows: the catalyst is dispersed in a mixed system composed of ultrapure water, anhydrous ethanol and naphthol solution, ultrasonically formed into a slurry, and then drop-coated onto carbon paper at 40-60℃ in a protective gas to obtain the cathode; Furthermore, the catalyst density on the carbon paper is specified to be 0.5-2 mg / cm³. 2 .

[0009] Furthermore, the catalyst density on the carbon paper is specified as 1 mg / cm³. 2 .

[0010] Further specifying, the catalyst preparation method includes the following steps: Step 1: Acidify and reflux the multi-walled carbon nanotubes, wash them until pH ≥ 6, freeze dry them, disperse the carbon nanotubes with open ends in acetone, and sonicate them to obtain a multi-walled carbon nanotube dispersion. Step 2: Dissolve the copper source in acetone, mix it with the multi-walled carbon nanotube dispersion, disperse it ultrasonically, and then vacuum dry it to obtain the copper source material encapsulated by carbon nanotubes. Step 3: Pyrolyze the copper source material encapsulated in carbon nanotubes in air or a protective gas. The product is then washed, vacuum dried, and ground to obtain copper oxide encapsulated in carbon nanotubes. Step 4: Place the phosphorus source above the copper oxide wrapped in carbon nanotubes and pyrolyze it in a protective gas. The product is then washed, vacuum dried, and ground to obtain the catalyst.

[0011] Furthermore, in step one, the length of the multi-walled carbon nanotubes is 2-50 μm and the inner diameter is 7-30 nm; the acid used for acidification is nitric acid or a solution of nitric acid and sulfuric acid mixed in a volume ratio of 3:1; the acidification reflux temperature is 120-140℃ and the time is 10-15 h.

[0012] Furthermore, the freeze-drying conditions in step one are: cold trap temperature -55℃, vacuum degree 0-5Pa, and time 24h.

[0013] Furthermore, in step two, the ultrasonic power is 300-480W; the copper source is copper acetate or copper nitrate; and the concentration of the copper source in acetone is 0.2-3g / L.

[0014] Furthermore, in step three, the vacuum drying temperature is 40-60℃, the time is 12h; the protective gas atmosphere is nitrogen or argon; and the gas flow rate of air or protective gas is 20-40mL / min.

[0015] Furthermore, in step three, the pyrolysis temperature is 200-450℃, the time is 2-5h, and the heating rate is 1-3℃ / min.

[0016] Furthermore, the vacuum drying temperature in step three is 40-60℃, and the time is 6 hours.

[0017] Further specifying, in step four, the phosphorus source is anhydrous sodium phosphite or anhydrous sodium hypophosphite; the protective gas is nitrogen or argon; the pyrolysis temperature is 250-450℃, the time is 2-4h, the heating rate is 1-3℃ / min, and the mass ratio of phosphorus source to copper oxide encapsulated by carbon nanotubes is 1:(2-10).

[0018] The second objective of this invention is to provide an application of the above-mentioned electrochemical treatment method for nitrate wastewater in the electrocatalytic synthesis of ammonia from nitrates.

[0019] A third objective of this invention is to provide an apparatus for the above-mentioned electrochemical treatment of nitrate wastewater, the apparatus comprising a cathode, a cathode chamber, a cation exchange membrane, a salt chamber, an anion exchange membrane, an acid chamber, a bipolar membrane, an alkali chamber, an anode chamber, an anode, and a hollow fiber gas diffusion membrane.

[0020] The beneficial effects of this invention are as follows: This invention confines phosphorus-doped copper oxide within carbon nanotubes and prepares an electrode by co-blending the catalyst with a naphthol solution, serving as the cathode. An electrolytic cell is constructed using a cascaded configuration of a bipolar membrane and a cation exchange membrane, achieving the removal of nitrates from wastewater and simultaneously and efficiently converting them to ammonium salts in a neutral environment. Compared to existing technologies, this invention also has the following advantages: (1) This invention provides a method for electrocatalytic simultaneous ammonia production and fixation of nitrate wastewater using an anion exchange membrane, a cation exchange membrane, and a bipolar membrane arranged in a stepped manner. Independent acid and alkali chambers are achieved through the arrangement of the bipolar membrane and anions / cations under an electric field. The ammonia-containing solution reduced in the cathode chamber is fixed in the acid chamber as ammonium salts using a hollow fiber gas diffusion membrane. As electrolysis continues, nitrates are ultimately fixed as ammonium salts in the acid chamber, while sodium hydroxide can be recovered in the alkali chamber. Specifically: During electrolysis, the liquid in the cathode chamber is pumped into the inner wall of the hollow fiber gas diffusion membrane. The cathode liquid does not mix with the solution in the acid chamber as it flows through the inner wall of the hollow fiber gas diffusion membrane; only high-concentration ammonia gas is allowed to diffuse into the solution in the acid chamber and combine with the acid to be fixed as ammonium salts. In other words, high-concentration ammonia in the cathode liquid diffuses into the acid chamber through the hollow fiber gas diffusion membrane and reacts with H+. + The bound material is converted into ammonium salt and fixed. The H₂ produced by the bipolar membrane during electrolysis... + As the sulfate ions move towards the cathode, they move from the salt chamber to the acid chamber, replenishing the H+ ions in the acid chamber. + With SO4 2 Content. OH generated by the bipolar membrane in the anodic direction. Na moves towards the anode, and Na in the cation anode chamber... + It moves towards the alkali chamber, where a sodium hydroxide solution is formed.

[0021] (2) This invention uses carbon nanotubes as a carrier. The carbon nanotubes are opened at both ends through acidification and reflux, followed by two high-temperature pyrolysis processes to form a phosphorus-doped copper oxide catalyst embedded within the carbon nanotubes. Utilizing the capillary action of the carbon nanotubes, a copper source solution is blended with the open carbon nanotubes and ultrasonically dried under vacuum to embed the copper salt within the carbon nanotubes. Pyrolysis is performed in air or a protective gas environment, where the copper salt is pyrolyzed in situ inside the carbon nanotubes to form copper oxide. A second high-temperature pyrolysis under a protective gas atmosphere alters the copper oxide lattice with phosphorus doping. Specifically, phosphorus atoms are doped by replacing the original copper / oxygen atom sites in the copper oxide lattice. The high conversion characteristics of copper oxide to nitrates enhance nitrate conversion. Phosphorus doping weakens excessive hydrogen evolution from copper oxides, while the two-dimensional structure of the carbon nanotubes further optimizes the interfacial water supply, preventing the hydrogen evolution reaction.

[0022] (3) The catalyst preparation method of the present invention enables the active sites to be fully dispersed inside the carbon nanotubes. During the pyrolysis process, the phosphorus element is in a gaseous state. The gaseous phosphorus doping makes the modification more uniform, which improves the nitrate conversion and ammonia selectivity.

[0023] (4) By controlling the amount of phosphorus source added, the proportion of phosphorus entering the copper oxide lattice is regulated, the electronic structure of the copper core is optimized, the adsorption of nitrate is enhanced, and the hydrogen supply of the oxide is also changed, so that the carbon nanotubes with built-in phosphorus doped copper oxide exhibit excellent catalytic performance and can effectively promote the electrocatalytic nitrate reduction reaction. Attached Figure Description

[0024] Figure 1 This is a schematic diagram illustrating the formation of carbon nanotubes with built-in phosphorus-doped copper oxide in this invention. Figure 2 Here is a SEM image of the catalyst prepared in Example 1; Figure 3 This is the EDS spectrum of the catalyst prepared in Example 1; Figure 4 These are the XRD patterns of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2; Figure 5 This is a schematic diagram of the apparatus for electrochemical treatment of nitrate wastewater according to the present invention; Figure 6 The results show the nitrate removal rate, ammonia selectivity, and ammonia recovery rate in Comparative Example 1. Figure 7 These are the results of nitrate removal rate, ammonia selectivity, and ammonia recovery rate in Example 1; Figure 8 These are the results of nitrate removal rate, ammonia selectivity, and ammonia recovery rate in Example 2; Figure 9 The results show the nitrate removal rate, ammonia selectivity, and ammonia recovery rate in Comparative Example 2. Among them, 1 is the cathode, 2 is the cathode chamber, 3 is the cation exchange membrane, 4 is the salt chamber, 5 is the anion exchange membrane, 6 is the acid chamber, 7 is the bipolar membrane, 8 is the alkali chamber, 10 is the anode chamber, 11 is the anode, and 12 is the hollow fiber gas diffusion membrane. Detailed Implementation

[0025] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0026] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0029] In the following methods, M represents the molar concentration in mol / L.

[0030] The following will refer to Figure 5 To illustrate the water treatment method of the present invention, Figure 5 In the diagram, 1 is the cathode, 2 is the cathode chamber, 3 is the cation exchange membrane, 4 is the salt chamber, 5 is the anion exchange membrane, 6 is the acid chamber, 7 is the bipolar membrane, 8 is the alkali chamber, 10 is the anode chamber, 11 is the anode, and 12 is the hollow fiber gas diffusion membrane. The liquid in cathode chamber 2 is the catholyte. The catalyst is prepared as a slurry and dripped onto carbon paper, which serves as cathode 1 and is fixed in cathode chamber 2. Figure 5 In the electrocatalytic nitrate reduction to ammonia simultaneous fixation device, the chambers from left to right are, in order: cathode chamber 2, salt chamber 4, acid chamber 6, alkali chamber 8, and anode chamber 10. The solutions in each chamber are, in order: 0.1M sodium sulfate (pH 6), 500 mg N / L sodium nitrate solution (pH 6), 0.1M sodium sulfate solution, 0.1M dilute sulfuric acid, pure water, and 0.1M sodium sulfate solution. The anode 11 is a platinum sheet. Cation exchange membranes 3, 5, and 7 are sequentially installed between cathode chamber 2, salt chamber 4, acid chamber 6, alkali chamber 8, and anode chamber 10. Cathode chamber 2, salt chamber 4, acid chamber 6, alkali chamber 8, and anode chamber 10 are all made of glass or PTFE. The cation exchange membranes 3, 5, and 7 are connected to the other chambers via gaskets. A hollow fiber gas diffusion membrane 12 is installed in acid chamber 6. This invention uses an Ag / AgCl electrode as a reference electrode and a sodium nitrate solution containing 0.1M sodium sulfate and 500mg N / L to simulate nitrate-polluted water. The water to be treated is added only to the cathode chamber 2.

[0031] The catholy liquid passes through the hollow fiber gas diffusion membrane 12 at a rate of 1-5 mL / min; the sodium sulfate concentration in the salt chamber 4 can be 0.1-0.5 M, and sodium sulfate should be replenished in time when the concentration is lower than 0.01 M; the anolyte can be a sodium hydroxide solution or a sodium sulfate solution. When the anolyte is sodium hydroxide, the alkali chamber 8 can be mixed with the anolyte to maintain the alkali concentration in both chambers; when the anolyte is sodium sulfate, by maintaining the control of the anode 11, the oxygen evolution reaction is used to promote the diffusion of acid to the alkali chamber 8, thereby obtaining a higher concentration of sodium hydroxide solution in the alkali chamber 2.

[0032] This invention employs a three-electrode system, with the catalyst used as the working electrode, i.e., the cathode, the reference electrode being an Ag / AgCl electrode, and the counter electrode being a platinum sheet as the anode.

[0033] The conversion formula between the reversible hydrogen electrode and the reference electrode is as follows: .

[0034] Example 1 Step 1: Preparation of catalyst (1) 200 mg of multi-walled carbon nanotubes with a length of 2-50 μm and an inner diameter of 7-30 nm were uniformly dispersed in 100 mL of 65 wt.% concentrated nitric acid and kept at 140 °C for 12 h. The concentrated acid was used to open the carbon nanotubes so that the copper source could be introduced through capillary action. After the heat preservation was completed, the carbon nanotubes were washed with deionized water until the pH was ≥6, frozen at -20 °C for 12 h, and dried in a freeze dryer (cold trap temperature -55 °C, vacuum degree 0-5 Pa) for 24 h. Then the dried open carbon nanotubes were uniformly dispersed in 20 mL of acetone and sonicated at 300 W for 30 min to obtain a uniformly dispersed multi-walled carbon nanotube dispersion. (2) Dissolve 38 mg of copper nitrate trihydrate in 20 mL of acetone to obtain a copper-containing acetone solution, mix it with a multi-walled carbon nanotube dispersion, sonicate at 450 W for 4 h at a constant temperature of 25 °C, and then vacuum dry at 60 °C for 6 h to obtain a copper source material encapsulated by carbon nanotubes. (3) The copper source material wrapped in carbon nanotubes was heated to 450°C in a tube furnace at a rate of 2°C / min and held for 2 hours. The product was washed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain carbon nanotubes with built-in copper oxide, i.e., copper oxide wrapped in carbon nanotubes, denoted as CuO-CNT. (4) Place 0.05 g of sodium hypophosphite and CuO-CNT sequentially upstream and downstream of a tube furnace at a mass ratio of 1:4. Introduce argon gas at a rate of 20 mL / min, and heat to 300 °C at a rate of 1 °C / min under argon atmosphere. Hold at this temperature for 2 h. After rinsing the exhaust gas with 0.5 M copper sulfate solution, discharge the gas. Wash the product three times with deionized water, dry it under vacuum at 60 °C, and grind it thoroughly to obtain the catalyst, namely carbon nanotubes with built-in phosphorus-doped copper oxide, denoted as 0.05P-CuO-CNT. See the schematic diagram of the specific synthesis process. Figure 1 The microstructure of the catalyst is as follows Figure 2 As shown, the morphology of the carbon nanotubes was not changed by the two heating processes. Figure 3 The EDS spectrum of the catalyst shows that phosphorus has been successfully doped, and C, Cu, O, and P are uniformly dispersed without significant aggregation. Step 2: Disperse 5 mg of catalyst in a mixture of 200 μL ultrapure water, 270 μL anhydrous ethanol, and 30 μL naphthol solution (naphthol dissolved in a 5% (v / v) ethanol aqueous solution). Sonicate for 30 min to form a slurry. Drop-coat the slurry onto carbon paper (2 × 2.5 cm²) at 70°C in an argon atmosphere. 2 The catalyst density is 1 mg / cm³.2 Cathode 1 is obtained; Step 3: Fix cathode 1 from Step 2 in cathode chamber 2, and fix platinum sheet anode 11 in anode chamber 10. Use an Ag / AgCl electrode as the reference electrode. Add 0.1M sodium sulfate and 500mg N / L sodium nitrate solution, 0.1M sodium sulfate solution, 0.1M dilute sulfuric acid, pure water, and 0.1M sodium sulfate solution to the solutions in cathode chamber 2, salt chamber 4, acid chamber 6, alkali chamber 8, and anode chamber 10, respectively. Run the reaction at a constant potential of -0.7V vs. RHE for 4 hours. After the reaction is complete, take a sample to detect NO3. NO2 NH3 and NH4 in acid chamber 6 + concentration; Under the influence of an electric field, cathode 1 in cathode chamber 2 converts nitrate into NH3. As the electrocatalytic time increases, the synthesized NH3 disperses in the catholyte; Na+ in sodium sulfate in salt chamber 4... + SO4 migrates through cation exchange membrane 3 into cathode chamber 2. 2 The ammonia migrates through the anion exchange membrane 5 into the acid chamber 6. In the acid chamber, on one hand, an aqueous solution containing a high concentration of ammonia from the cathode chamber 2 flows back to the cathode chamber 2 through the inner wall of the hollow fiber gas diffusion membrane 12. During this process, the hydrophobic hollow fiber gas diffusion membrane 12 only allows ammonia to diffuse into the acid chamber 6 in gaseous form, where it combines with sulfuric acid to be fixed as ionic ammonium sulfate. On the other hand, SO42- from the anion exchange membrane 5 is received. 2 With bipolar film 7 H + The acid concentration is replenished; in anode chamber 10, an oxygen evolution reaction occurs on the surface of anode 11, and the Na in the anolyte... + It migrates through cation exchange membrane 3 into alkaline chamber 8, replenishing the concentration of alkaline chamber 8.

[0035] Example 2 The difference between this embodiment and embodiment 1 is that: in step (4) of step one, the sodium hypophosphite is 0.1g, the mass ratio of sodium hypophosphite to CuO-CNT is 1:2, and the resulting catalyst is denoted as 0.1P-CuO-CNT. Other process operations and parameter settings are the same as in embodiment 1.

[0036] Example 3 The difference between this embodiment and embodiment 1 is that: in step (4) of step one, the sodium hypophosphite is 0.02g, the mass ratio of sodium hypophosphite to CuO-CNT is 1:10, and the resulting catalyst is denoted as 0.02P-CuO-CNT. Other process operations and parameter settings are the same as in embodiment 1.

[0037] Example 4 The difference between this embodiment and embodiment 1 is that the acetone in step (2) of step one is 190 mL, and the other process operations and parameter settings are the same as in embodiment 1.

[0038] Example 5 The difference between this embodiment and embodiment 1 is that the acetone in step (2) of step one is 12.7 mL, while the other process operations and parameter settings are the same as in embodiment 1.

[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that step (4) in step one was not performed, and the resulting catalyst is denoted as CuO-CNT. Other process operations and parameter settings are the same as in Example 1.

[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that: in step (4) of step one, the sodium hypophosphite is 0.2g, the mass ratio of sodium hypophosphite to CuO-CNT is 3:2, and the resulting catalyst is denoted as 0.2P-CuO-CNT. Other process operations and parameter settings are the same as in Example 1.

[0041] Figure 4 The images show the XRD patterns of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2. It can be seen that the main phase of the material is still copper oxide. The higher peak intensity in Examples 1-2 indicates higher crystallinity. The doping of phosphorus causes a shift in the peak position, indicating that phosphorus successfully enters the crystal lattice, leading to a change in the lattice constant.

[0042] Figure 6-9 The results for nitrate removal rate, ammonia selectivity, and ammonia recovery rate are respectively for Comparative Examples 1-2 and Examples 1-2. Ammonia selectivity refers to the conversion rate of ammonia in the removed nitrate (including ammonia in cathode chamber 2 and ammonium ions in acid chamber 6). Ammonia recovery rate refers to the recovery rate of nitrate reduced to ammonia and converted to ammonium ions in the acid chamber through the hollow fiber gas diffusion membrane. Figure 6 The results showed that after 4 hours of reaction, the nitrate removal rate of Comparative Example 1 reached 82.1%, and the concentration of ammonia generated was 330.5 mg / L, of which NH4 in acid chamber 6... + With a concentration of 292.8 mg / L, the ammonia recovery rate was 88.5%; with a nitrite concentration of 0.15 mg / L, the ammonia selectivity was 80.51%. The CuO-CNT catalyst in Comparative Example 1, due to its catalytic sites being embedded in the two-dimensional space of carbon nanotubes, optimized the supply of interfacial water, resulting in high selectivity for ammonia nitrogen. However, the mismatch between the supply of active hydrogen from the copper oxide and the nitrate hydrogenation process led to a relatively severe hydrogen evolution side reaction.

[0043] Figure 7-9The effects of different levels of phosphorus doping on the treatment of high-concentration nitrate wastewater after 4 hours of reaction were demonstrated. The results of Examples 1-2 show that phosphorus doping can enhance nitrate conversion and ammonia selection. Example 1 exhibited the highest nitrate conversion rate, achieving 98.72% nitrate removal from the water to be treated, generating an ammonia nitrogen concentration of 453.9 mg / L, and reducing NH4 in acid chamber 6. + The concentration was 420.58 mg / L, and the ammonia recovery rate reached 92.6%, meaning that 92.6% of the generated ammonia was recovered in the form of ammonium ions (ammonium sulfate); the nitrite concentration was 0.12 mg / L, and the ammonia selectivity was as high as 91.96%. The nitrate removal efficiency of Example 2 was slightly lower than that of Example 1. Unlike Example 1, in Comparative Example 2, the presence of an excessive phosphorus source led to the excessive reduction of copper oxides. The phosphorus was no longer incorporated into the crystals but formed copper-phosphorus compounds, resulting in poor electrocatalytic efficiency.

[0044] The above results demonstrate that this invention utilizes carbon nanotubes with embedded phosphorus-doped copper oxide as a catalyst, and further as a cathode in... Figure 5 The device can efficiently electrocatalytically reduce nitrate to ammonia, and the stepped arrangement of the ion exchange membrane can efficiently fix and recover the ammonia generated in the cathode chamber.

[0045] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method of electrochemically treating nitrate waste water, characterized by, The method is as follows: using an electrode prepared with a catalyst as the cathode, Ag / AgCl as the reference electrode, and a platinum sheet, ruthenium-iridium-titanium electrode, or boron-doped diamond electrode as the anode, water containing nitrate is electrolyzed; the catalyst is a carbon nanotube with built-in phosphorus-doped copper oxide. The catalyst preparation method includes the following steps: Step 1: Acidify and reflux the multi-walled carbon nanotubes, wash them until pH ≥ 6, freeze dry them, disperse the carbon nanotubes with open ends in acetone, and sonicate them to obtain a multi-walled carbon nanotube dispersion. Step 2: Dissolve the copper source in acetone, mix it with the multi-walled carbon nanotube dispersion, disperse it ultrasonically, and then vacuum dry it to obtain the copper source material encapsulated by carbon nanotubes. Step 3: Pyrolyze the copper source material encapsulated in carbon nanotubes in air or a protective gas. The product is then washed, vacuum dried, and ground to obtain copper oxide encapsulated in carbon nanotubes. Step 4: Place the phosphorus source above the copper oxide wrapped in carbon nanotubes and pyrolyze it in a protective gas. The product is then washed, vacuum dried and ground to obtain the catalyst. In step three, the pyrolysis temperature is 200-450℃, the time is 2-5h, and the heating rate is 1-3℃ / min. In step four, the phosphorus source is anhydrous sodium phosphite or anhydrous sodium hypophosphite, the protective gas is nitrogen or argon, the pyrolysis temperature is 250-450℃, the time is 2-4h, the heating rate is 1-3℃ / min, and the mass ratio of phosphorus source to copper oxide encapsulated by carbon nanotubes is 1:(2-10). The device used for the electrochemical treatment of nitrate wastewater includes a cathode, a cathode chamber, a cation exchange membrane, a salt chamber, an anion exchange membrane, an acid chamber, a bipolar membrane, an alkali chamber, an anode chamber, an anode, and a hollow fiber gas diffusion membrane.

2. The method of claim 1, wherein, The cathode is prepared by dispersing the catalyst in a mixed system consisting of ultrapure water, anhydrous ethanol and naphthol solution, ultrasonically forming a slurry, and then drop-coating it onto carbon paper at 40-60°C in a protective gas atmosphere to obtain the cathode.

3. The method of claim 2, wherein, The catalyst density on the carbon paper was 0.5-2 mg / cm 2 .

4. The method according to claim 1, characterized in that, In step one, the length of the multi-walled carbon nanotubes is 2-50 μm and the inner diameter is 7-30 nm. The acid used for acidification is nitric acid or a solution of nitric acid and sulfuric acid in a volume ratio of 3:

1. The acidification reflux temperature is 120-140℃ and the time is 10-15 h.

5. The method according to claim 1, characterized in that, In step two, the ultrasonic power is 300-480 W, the copper source is copper acetate or copper nitrate, and the copper source concentration in acetone is 0.2-3 g / L.

6. The method according to claim 1, characterized in that, In step three, the vacuum drying temperature is 40-60℃, the time is 12h, the protective gas atmosphere is nitrogen or argon, and the gas flow rate of air or protective gas is 20-40mL / min.

7. The application of the electrochemical treatment method for nitrate wastewater according to any one of claims 1-6 in the electrocatalytic synthesis of ammonia from nitrate.

Citation Information

Patent Citations

  • Carbon-based copper-nickel composite electrode for reducing nitrate nitrogen in water as well as preparation method and application of composite electrode

    CN108585125A

  • Persulfate activation catalyst prepared from modified carbon nanotubes and preparation method and application thereof

    CN108993491A

  • Sewage treatment method, adopted sewage treatment agent and preparation method of sewage treatment agent

    CN116161768A

  • Catalyst applied to ammonia production through electro-catalysis nitrate reduction and preparation method of catalyst

    CN122446248A